2009
DOI: 10.4161/cbt.8.8.7834
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor Cells in the context of treatment: Prognostic value in breast cancer patients

Abstract: Circulating tumor cells (CTCs) in patients with breast cancer can be regarded as the pre-stadium of clinically manifest distant metastases. Here we present results on CTCs determination in peripheral blood (PB) of breast cancer patients in the context of treatment.Ninety-two patients were enrolled onto a prospective, unicenter study and 71 of those subjects are the focus of our analyses. The differential prognostic and overall survival showed between patients with and without elevated CTCs before and at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
1
23
1
2
Order By: Relevance
“…Some studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) showed that the presence of CTC was significantly associated with shorter survival in breast cancer. In contrast, other studies (14)(15)(16)(17)(18)(19)(20) failed to show such an association between the presence of CTC and worse prognosis. This discrepancy may result from the rather small sample size of patients enrolled in these studies as well as differences in the time point of blood collection and CTC assays used.…”
Section: Introductioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Some studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) showed that the presence of CTC was significantly associated with shorter survival in breast cancer. In contrast, other studies (14)(15)(16)(17)(18)(19)(20) failed to show such an association between the presence of CTC and worse prognosis. This discrepancy may result from the rather small sample size of patients enrolled in these studies as well as differences in the time point of blood collection and CTC assays used.…”
Section: Introductioncontrasting
confidence: 44%
“…In 12 studies (6,13,16,17,19,32,34,35,37,39,41,48), more than 1 HR was extracted from each study because multimarkers or multitime points were used to detect CTC in these studies and HRs were reported separately.…”
Section: Global Analysis Of Ctc Effects On Survivalmentioning
confidence: 99%
“…Similar results were observed by Hartkopf et al (2011). Instead of using cutoff point of 5 CTCs, Serrano et al (2009) established a cutoff point of 6 CTCs to validate the clinical outcome. Tewes et al (2009) reported that the concordance between clinical response and CTC levels measured over the course of palliative treatment reached 78%.…”
Section: Breast Cancermentioning
confidence: 99%
“…In addition to the 'tumour marker' function of CTCs, these cells remain in the lymphatic/systemic circulation after surgical removal of the primary tumour and are responsible for the later recurrence of the disease. Consequently this undetected cell dissemination by conventional measures is of relevance for cancer progression and has been already demonstrated to be of prognostic impact in several malignancies [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%